Properties and Characteristics of Certain Subclass of Analytic Functions with Positive Coefficients (Tamsui Oxford Journal of Mathematical Sciences)
In this paper, the authors introduce and investigate the various properties and characteristics of subclass M+n (∞β) of analytic functions with positive coefficient estimates, Hadamard products, distortion theorems, covering theorems and (n,δ)-neighborhoods are proven here for this function class. Furthermore, some interesting distortion theorems for the Srivastava-Saigo-Owa fractional integral operator are also obtained.